2017
DOI: 10.3748/wjg.v23.i15.2750
|View full text |Cite
|
Sign up to set email alerts
|

Association of obesity withHelicobacter pyloriinfection: A retrospective study

Abstract: AIMTo explore the association between Helicobacter pylori (H. pylori) infection and obesity/weight gain in a Chinese population.METHODSOur primary outcome was the change in body mass index (BMI). The generalized linear models were used to explore the association between H. pylori infection and the change of BMI, and the logistic regression models were used to explore the association between H. pylori infection and obesity.RESULTSA total of 3039 subjects were recruited and analyzed, of which 12.8% were obese. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
1
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(26 citation statements)
references
References 23 publications
(29 reference statements)
2
21
1
2
Order By: Relevance
“…However, other BMI groups showed no difference compared with the normal BMI group. And the association between obesity and H. pylori infection is controversial, and the causality of these associations has not been proven 2, 21, 22. We also investigated the correlation between BMI and residence style after high school (city vs noncity) but observed no significant correlation between the two (data not shown).…”
Section: Discussionmentioning
confidence: 89%
“…However, other BMI groups showed no difference compared with the normal BMI group. And the association between obesity and H. pylori infection is controversial, and the causality of these associations has not been proven 2, 21, 22. We also investigated the correlation between BMI and residence style after high school (city vs noncity) but observed no significant correlation between the two (data not shown).…”
Section: Discussionmentioning
confidence: 89%
“…Among 13 autoimmune diseases evidence in support of a probable role of HPI was found in four—TP, Graves’ disease, neuromyelitis optica and psoriasis [ 361 ]. Just to mention some examples of contradictory conclusions: many reports and meta-analyses suggested a positive correlation between HPI, metabolic associated fatty liver disease (MAFLD; previous term non-alcoholic fatty liver disease, NAFLD) [ 362 , 363 , 364 , 365 , 366 , 367 , 368 , 369 , 370 , 371 , 372 ], type 2 diabetes mellitus (DM)/insulin resistance [ 373 , 374 , 375 , 376 , 377 ], diabetic complications [ 378 , 379 , 380 ] and obesity [ 381 , 382 ], whereas others did not found such associations [ 383 , 384 , 385 , 386 , 387 , 388 , 389 ] and some described an inverse correlation of HPI with obesity [ 390 , 391 , 392 ]. Similarly, there is discrepancy between various studies regarding links between HPI and cardiovascular diseases (CVD) [ 333 , 393 , 394 , 395 , 396 , 397 , 398 , 399 , 400 ].…”
Section: Hpi-associated Chronic Extra-gastroduodenal Diseases Medmentioning
confidence: 99%
“…HPI has been reported to increase the risk of adult-onset asthma [ 443 ] and systemic lupus erythematosus [ 444 ]. A significantly higher HPI incidence rate was found in patients with Sjogren syndrome [ 445 ], autoimmune thyroid disease [ 446 , 447 , 448 ], multiple sclerosis [ 447 , 448 ] and no association between HPI and body mass index/obesity was observed in different populations [ 388 , 449 , 450 ]. The huge heterogeneity of asthma and other mentioned above diseases may, at least partially, contribute to the controversies in the publications.…”
Section: Hpi-associated Chronic Extra-gastroduodenal Diseases Medmentioning
confidence: 99%
“…But the relationship between H. pylori infection and obesity remains controversial [2][3][4][5][6][7]. Some studies identified a positive correlation [3,[8][9][10], while others found a negative correlation [4,7] or even no correlation [2,11]. A meta-analysis of 18 observational studies involving over 10,000 subjects found a higher body mass index (BMI) among H. pylori-positive subjects compared with H. pylori-negative subjects [12].…”
Section: Introductionmentioning
confidence: 99%